Carbon dioxide emission and bio-capacity indexing for transportation activities: A methodological development in determining the sustainability of vehicular transportation systems. (1st October 2018) - Labib, S.M.; Neema, Meher Nigar; Rahaman, Zahidur; Patwary, Shahadath Hossain; Shakil, Shahadat Hossain
Abstract: CO2 emissions from urban traffic are a major concern in an era of increasing ecological disequilibrium. Adding to the problem net CO2 emissions in urban settings are worsened due to the decline of bio-productive areas in many cities. This decline exacerbates the lack of capacity to sequestrate CO2 at the micro and meso-scales resulting in increased temperatures and decreased air quality within city boundaries. Various transportation and environmental strategies have been implemented to address traffic related CO2 emissions, however current literature identifies difficulties in pinpointing these critical areas of maximal net emissions in urban transport networks. This study attempts to close this gap in the literature by creating a new lay-person friendly index that combines CO2 emissions from vehicles and the bio-capacity of specific traffic zones to identify these areas at the meso-scale within four ranges of values with the lowest index values representing the highest net CO2 levels. The study used traffic volume, fuel types, and vehicular travel distance to estimate CO2 emissions at major links in Dhaka, Bangladesh's capital city's transportation network. Additionally, using remote-sensing tools, adjacent bio-productive areas were identified and their bio-capacity for CO2 sequestration estimated. The bio-productive areas were correlated with each traffic zone under study resulting in an Emission Bio-Capacity index (EBI) value estimate for each traffic node. Among the ten studied nodes in Dhaka City, nine had very low EBI values, correlating to very high CO2 emissions and low bio-capacity. As a result, the study considered these areas unsustainable as traffic nodes going forward. Key reasons for unsustainability included increasing use of motorized traffic, absence of optimized signal systems, inadequate public transit options, disincentives for fuel free transport (FFT), and a decline in bio-productive areas. Highlights: An Index to evaluate urban transportation sustainability is proposed. The index combines CO2 emissions from vehicle activities at meso-scale and local bio-capacities to sequestrate emissions. The index was tested in real world setting- Dhaka city, Bangladesh. Out of ten traffic nodes studies, nine nodes showed very higher CO2 emission and low bio-capacities. Reasons include, increase of private vehicles, lack of public transit, poor signal system, lack of bio-productive areas.